More than a face: a unified theoretical perspective on nonverbal social cue processing in social anxiety - Gilboa-Schechtman, Eva; Shachar-Lavie, Iris (Frontiers in Human Neuroscience, 2013)
Processing of nonverbal social cues (NVSCs) is essential to interpersonal functioning and is particularly relevant to models of social anxiety. This article provides a review of the literature on NVSC processing from the perspective of social rank and affiliation biobehavioral systems, based on functional analysis of human sociality. We examine the potential of this framework for integrating cognitive, interpersonal, and evolutionary accounts of social anxiety. We argue that NVSCs are uniquely suited to rapid and effective conveyance of emotional, motivational, and trait information and that various channels are differentially effective in transmitting such information. First, we review studies on perception of NVSCs through face, voice, and body. We begin with studies that utilized information processing or imaging paradigms to assess NVSC perception. This research demonstrated that social anxiety is associated with biased attention to, and interpretation of, emotional facial expressions and emotional prosody. Findings regarding body and posture remain scarce. Next, we review studies on NVSC expression, which pinpointed links between social anxiety and disturbances in eye gaze, facial expressivity, and vocal properties of spontaneous and planned speech. Again, links between social anxiety and posture were understudied. Although cognitive, interpersonal, and evolutionary theories have described different pathways to social anxiety, all three models focus on interrelations among cognition, subjective experience, and social behavior. NVSC processing and production comprise the juncture where these theories intersect. In light of the conceptualizations emerging from the review, we highlight several directions for future research including focus on NVSCs as indexing reactions to changes in belongingness and social rank, the moderating role of gender, and the therapeutic opportunities offered by embodied cognition to treat social anxiety.